Degradation of Humic Acid by Ferrous Ion Activated Persulfate. Issue 2 (February 2020) - Zhang, Qinqin; He, Xu; Ding, Shimin; Feng, Xianghua; Yu, Youqing
Abstract: The persulfate anions (S2 O8 2™ ) can be activated by Fe 2+ to produce sulfate radicals (·SO4 − ) and hydroxyl radicals (·OH), which can oxidize organic compounds rapidly. Humic acid (HA) is widely found in nature and is the main limiting factor for high-concentration wastewater discharge. In this study, HA was treated by Fe 2+ /S2 O8 2™ system, the effects of initial pH, concentrations of Fe 2+, persulfate (PS), and HA on the removal efficiencies of HA and E3 /E4 were discussed. Besides UV254 and UV280, we found that UV250, UV270, UV300, UV365, UV400, UV436 and UV465 can effectively quantified the concentrations of HA, providing more HA characterization methods. When the initial pH was 3.0, the concentrations of PS and Fe 2+ were 100 mmol/L and 20 mmol/L, respectively, the removal efficiency of HA reached 72% after 5 minutes, indicating that PS/Fe 2+ effectively degrade HA, and E3 /E4 increased from 2.6 to 5.75, suggesting the molecular weight and aromaticity of HA decreased. The removal efficiencies of HA increased as the concentrations of Fe 2+ and PS increased, while the removal efficiencies of HA decreased as the initial concentration of HA increased. The addition of hydroxylamine hydrochloride (HAH) in Fe 2+ /S2 O8 2™ system, could effectively promoted the Fe 3+ /Fe 2+ circulation and reduced the accumulation of Fe 3+, and strengthened the removal efficiency of HA. The research results indicate that Fe 2+ /S2 O8 2™ oxidation is a promising technique for the treatment of HA in wastewater.